2020
DOI: 10.3390/f11060672
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Paeonia rockii (Flare Tree Peony) Germplasm Accessions Revealed by Phenotypic Traits, EST-SSR Markers and Chloroplast DNA Sequences

Abstract: Research Highlights: This study, based on the first collection of cultivated Paeonia rockii (flare tree peony, FTP) germplasm across the main distribution area by our breeding desires, comprehensively evaluates these accessions by using phenotypic traits, expressed sequence tag (EST)-simple sequence repeat (SSR) markers and chloroplast DNA sequences (cpDNA). The results show that these accessions collected selectively by us can represent the genetic background information of FTP as a germplasm of tree crops. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Then, the two methods were utilized to evaluate population structure and produced coincident consequences. Through STRUCTURE analysis, the 160 accessions were divided into three subgroups, and to a large extent, this was supported by the NJ tree analysis, which was similar to previous reports of three subgroups in FTP ( Wu et al, 2017 ; Guo et al, 2020 ). Furthermore, Yuan et al (2012) revealed that 335 wild P. rockii individuals were mainly divided into three subpopulations, which were strongly linked to the geographical distribution pattern of wild P. rockii .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Then, the two methods were utilized to evaluate population structure and produced coincident consequences. Through STRUCTURE analysis, the 160 accessions were divided into three subgroups, and to a large extent, this was supported by the NJ tree analysis, which was similar to previous reports of three subgroups in FTP ( Wu et al, 2017 ; Guo et al, 2020 ). Furthermore, Yuan et al (2012) revealed that 335 wild P. rockii individuals were mainly divided into three subpopulations, which were strongly linked to the geographical distribution pattern of wild P. rockii .…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, it was very important to use molecular markers to analyze genetic diversity and population structures. In this study, 81 SSRs detected a total of alleles in 160 accessions, and the N A was 6.09, which was larger than SSRs in individuals (N A = 4.5; Wu et al, 2017) and 34 SSRs in 282 cultivars (N A = 5.441; Guo et al, 2020), but smaller than 12 SSRs in 335 individuals of wild P. rockii (N A = 9.15; Yuan et al, 2012). This suggested that, on the one hand, the SSR primers and plant materials used in this study had comparatively higher allele variation, and on the other hand, the diverse primers and materials used in the studies gave rise to discrepancies.…”
Section: Genetic Diversity Of the Associated Populationmentioning
confidence: 49%
See 1 more Smart Citation
“…The cork drop is pink with protruding lenticels while the inner surface is light brown or gray-yellow with a fine longitudinal texture and shiny crystals. It has a special aroma and a slightly bitter taste (18). and triterpenoids, especially phenols (19)(20)(21)(22).…”
Section: Botanical Characteristicsmentioning
confidence: 99%
“…The study by Guo et al [8] was based on the first collection of cultivated Paeonia rockii (flare tree peony, FTP) germplasm, across the main distribution area. Using phenotypic traits, expressed sequence tag (EST)-simple sequence repeat (SSR) markers and chloroplast DNA sequences (cpDNA), the authors showed that the selected accessions could fully reflect the genetic background information of FTP germplasm resources, so their protection and utilization would be of great significance for genetic improvement of woody peonies.…”
mentioning
confidence: 99%